Codes of practice and reduced impact logging in tropical forests: an overview - Applegate, G. (ATSE Crawford Fund, 2002)
This paper highlights how early experience gained in north Queensland rainforests provided input to the development of Pacific island codes and the code of conduct for logging of indigenous forests in selected South Pacific countries in the mid-1990s. In a number of these countries, the development of codes of practice has been undertaken in parallel with the preparation of reduced impact guidelines and improved silvicultural practices. The work in the Pacific has recently been extended to include Asia with the publishing of the code of practice for forest harvesting in Asia-Pacific developed for the Asia Pacific Forestry Commission in 1999. A number of countries in this region are now developing their own national codes based on the Asia-Pacific code. Impediments to adoption of codes of practice are highlighted, along with some of the issues relating to costs as an impediment. Some of the research initiatives are aimed at analysing who pays the costs, who should pay and who benefits in the short and long term from improved timber harvesting practices.